(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The aim of the research was to study the influence of mineral fertilizers and liming on yields of field crops and agrochemical parameters of soil and loss of plant nutrients through drain water. Since 1982, long-term field trials were carried out under crop succession with long-term grass, grain (rye, triticale, spring wheat, barley, oat), potatoes and rape. Annually from soil thought drains were leached about 3.0 - 21.9 kg ha-1 nitrogen, 0.1 - 0.5 kg ha'1 and 0.6 -1.7 kg ha-1 potassium. Application of P0 and P30 led to the further decrease of phosphorus content as fa r as 0-6 mg kg especially in limed soil. Significant increase of phosphorus content was observed only using phosphorus rate P90. Positive NPK balance in limed trial plots was achieved with annual inputs of 90 kg ha-1 N, 100 kg ha-1 P20 s and 90 Kg ha-1 K20.